Preliminary Exploration on the Value of Shear Wave Elastography in Evaluating the Effectiveness of Microwave Ablation on Hepatic Malignancies. Issue 2 (8th June 2022) - Luo, Chunyue; Lin, Jianying; Liu, Guancheng; He, Guangmin; Zuo, Yanling; Dai, Lu; Li, Tao
Abstract: Shear wave elastography (SWE) is a new type of ultrasonic elastography that can quantitatively assess the elasticity and stiffness of tissues. This study aimed to investigate the value of SWE in evaluating the effectiveness of microwave ablation in hepatic malignancies. A total of 24 patients (including 30 lesions) with liver malignancies receiving microwave ablation treatment at the Cancer Hospital of Guangzhou Medical University from April 2018 to January 2019 were enrolled. The elastography was performed within 1 week before and after ablation. The SWE values in the central zone, the marginal zone of the lesion, and peripheral liver parenchyma were collected and analyzed. Before ablation, the mean of SWE value was 65.80 ± 13.37 kPa for the central zone of the tumor and 39.93 ± 7.87 kPa for the marginal zone, both of which were significantly greater than that for the perinatal liver parenchyma (12.85 ± 2.67 kPa, both P < 0.05). In the central and marginal zone of the lesions, the SWE value was significantly elevated after ablation (both P < 0.001) but not in the peripheral liver parenchyma ( P = 0.444). Receiver operating characteristic curve analysis showed that the cutoff value for ablation in the marginal zone was 53.87 kPa, suggesting that an SWE exceeding 53.87 kPa is an index guaranteeing the ablation effectiveness. These results suggested that SWE has the potential to be used in evaluating the effectiveness of microwave ablation in liver cancers.